Genetic Dissection of the Canq1 Locus Governing Variation in Extent of the Collateral Circulation - Shiliang Wang; Hua Zhang; Tim Wiltshire; Robert Sealock; James E. Faber (2012)
Background Native (pre-existing) collaterals are arteriole-to-arteriole anastomoses that interconnect adjacent arterial trees and serve as endogenous bypass vessels that limit tissue injury in ischemic stroke, myocardial infarction, coronary and peripheral artery disease. Their extent (number and diameter) varies widely among mouse strains and healthy humans. We previously identified a major quantitative trait locus on chromosome 7 (Canq1, LOD = 29) responsible for 37% of the heritable variation in collateral extent between C57BL/6 and BALB/c mice. We sought to identify candidate genes in Canq1 responsible for collateral variation in the cerebral pial circulation, a tissue whose strain-dependent variation is shared by similar variation in other tissues. Methods and Findings Collateral extent was intermediate in a recombinant inbred line that splits Canq1 between the C57BL/6 and BALB/c strains. Phenotyping and SNP-mapping of an expanded panel of twenty-one informative inbred strains narrowed the Canq1 locus, and genome-wide linkage analysis of a SWRxSJL-F2 cross confirmed its haplotype structure. Collateral extent, infarct volume after cerebral artery occlusion, bleeding time, and re-bleeding time did not differ in knockout mice for two vascular-related genes located in Canq1, IL4ra and Itgal. Transcript abundance of 6 out of 116 genes within the 95% confidence interval of Canq1 were differentially expressed >2-fold (p-value<0.05÷150) in the cortical pia mater from C57BL/6 and BALB/c embryos at E14.5, E16.5 and E18.5 time-points that span the period of collateral formation. Conclusions These findings refine the Canq1 locus and identify several genes as high-priority candidates important in specifying native collateral formation and its wide variation.